Does geographic dispersion affect firm valuation? - Gao, Wenlian; Ng, Lilian; Wang, Qinghai (Journal of Corporate Finance, 2008)
We find that the geographic dispersion of a corporation affects its firm valuation. Firms with subsidiaries located in different regions of the United States experience a valuation discount of 6.2% after controlling for the impact of both global and industrial diversifications. The valuation discount increases as firms expand their operations to different regions nationwide. Results show that firms with more anti-takeover provisions are more likely to be geographically diverse, and that these firms experience greater value discounts compared with their counterparts with fewer such provisions. Our overall evidence suggests that the geographic location of corporate activities is an essential component of corporate policies and has important market valuation implications.